Prevalence of anaemia among adolescent girls: a case Study based on Sandilipay medical officer of health area, Jaffna district - Menaka, S.; Arasaratnam, V.; Surendrakumaran, R. (South Eastern University of Sri Lanka, 2024)
Anemia is a significant health concern among adolescents, as the rapid growth and development takes place in this stage. The aim of the study was to assess the prevalence of anaemia among adolescents in Sandilipay Medical officer of Health (MOH) area of Jaffna district. Socio- demographic information was collected with an interviewer administrated questionnaire during household visits. Ethics review committee, Faculty of Medicine, University of Jaffna gave the ethical approval for the study. Blood samples were collected from 92 adolescents for the analysis of red blood cell indices by cyanmethemoglobin method. Among the adolescents 54 were females (58.7%) with the mean age of 18.07 (±0.8) years. The mean haemoglobin (Hb) concentration among female adolescents was 12.05 (±1.8) g/dl (range 7.4 to 15.3 g/dl) and that of the male adolescents was 15.69 (±1.4) g/dl (range 13.9 to 18.5 g/dl). Among the adolescents, 37% (n=20) were anaemic (Hb levels <11.9 g/dl) and all were females. Mean hematocrit (HCT) and mean corpuscular volume (MCV) of the female adolescents were 36.4 (±4.1) % and 80.8 (±9.8) fl respectively. Among the female adolescents, 44% (n=24) had HCT level below 36%, and 37% (n=20) had MCV below 80 fL. Both indicated the prevalence of anemia. The prevalence of anemia among female adolescents in the Sandilipay MOH area is in significant number and the type of anaemia need to be studied in detail.
Keywords: Adolescents; Anaemia; Nutrition; Jaffna; Haemoglobin